Distribución espacial de Tinámidos (tinamiformes) en la Estación Biológica La Selva, Costa Rica (ING) - Oviedo Pérez, Paul E. (Uniciencia, 2008)
In the period from September to November 2003 I registered tinamids, using routes with variable radius through paths and transects of 200 m in four different habitats of La Selva Biological Station (10°25ʼ52.51"N, 84°00ʼ12.96"W). The objective of this study was to identify the sites that are frequent the most by the three different species of Tinamiformes of the area. I registered highest number of tinamous using transects of 200 m. Tinamus major was mainly found in primary forest, where it was very hard to observe, and in an abandoned agroforestry system, where it was very tolerant to the presence of humans. It was observed solitary or in group of up to five adult individuals. Crypturellus soui would concentrate more in areas that had an initial secondary growth, and was the specie most difficult to observe, it was registered as pairs and groups. Crypturellus boucardi is a uncommon specie, it was found solitary in different types of habitats.